Oral histories with Gypsy and traveller community members and prisoners, professional interviews, and crime survey data from the ESRC project 'Gypsy and Traveller Experiences of Crime and Justice Since the 1960s', 2020-2023 - Phillips, Coretta (UK Data Service, 2025)
The Realities Checked Study provides the first systematic and comprehensive account of the crime and criminal justice experiences of Gypsies and Travellers in England since the 1960s. Motivated by the need to challenge and critique popular stereotypes that portray Gypsies and Travellers as inherently criminal, the study seeks to provide a nuanced understanding of the community’s experiences with crime and the criminal justice system. The study’s primary aims were to examine: Gypsies’ and Travellers’ direct and vicarious perceptions of criminal victimisation, hate crimes, and offending; the role of perceived racism and discrimination in shaping offending behaviour and experiences with criminal justice; the impact of criminalisation, policing, punishment, and imprisonment on individuals and communities; and the rationales behind professional engagement with Gypsies and Travellers in the areas of crime, justice, and social policy. Conducted between October 2020 and June 2023, this dataset employs a mixed-methods approach, including a crime survey of 400 participants of Gypsy and Traveller heritage, 40 oral histories with Gypsy and Traveller community members, 27 oral histories with Gypsy and Traveller prisoners, and interviews with 54 professionals working with Gypsy and Traveller communities. Research took place across England, including Leeds, Norfolk, the South-East (London, Sussex, and Surrey), Devon, and Cornwall. Participants included Gypsies and Travellers living roadside, on sites, on private plots, and in bricks-and-mortar housing. The crime survey focused on gathering data about the frequency of discrimination, racism, and crime experienced by Gypsies and Travellers. The oral histories explored participants’ life stories, including childhood, young adulthood, and experiences with crime. Professional interviews examined the work of professionals and organisations engaging with Gypsies and Travellers in relation to crime and criminal justice. Historical accounts show that since the arrival in England and Scotland of Romani Gypsies in the fifteenth century, and of Irish Travellers in the nineteenth century, they have been associated with criminal offending. Since then Gypsies and Travellers (G&Ts) have become entrenched in popular, media and political imaginations as criminal predators, bringing property crime, violence, fraud, tax evasion and anti-social behaviour to settled communities. Yet despite five centuries' of such categorisation, there is surprisingly no rigorous evidence assessing the validity of such claims nor systematic assessments of G&Ts' experiences of victimisation. No existing sources of evidence from self-report offending surveys, archival accounts, oral histories, ethnographic or qualitative research can provide an estimate of G&T patterns of offending. Neither can they tell us about how frequently G&Ts are the victims of non-racially motivated crime (e.g. assault, burglary, theft) or hate crimes. This is particularly concerning given the Global Attitudes Survey found 50% of UK respondents held negative views of G&Ts, over double the proportion holding unfavourable attitudes towards Muslims, who have often been the victims of hate crimes. Estimates of offending, victimisation and hate crime are available for other minority ethnic groups. This interdisciplinary study will produce the first comprehensive, historicized account of G&T experiences of victimisation, crime and criminal justice in two urban and two rural areas of England. Specifically, it will comprise: (i) a crime survey involving researchers and G&T interviewers looking at G&T victimisation by personal crime (e.g. assault, hate crime) and crimes against the household/family (e.g. burglary, fraud). It will assess attitudes to, and contact with, the police (including stop and search), courts, probation, and prisons. The survey will also ask questions about G&Ts' use of alcohol/drugs and involvement in property, fraud, and violent offences as offenders. It will survey self-ascribing G&Ts who vary by gender, age and settlement (roadside living, official/private caravan sites, unauthorised encampments, and private/social housing); (ii) community and prisoner oral histories to investigate whether offending over individual lifetimes is linked to experiences of racism and discrimination, and to explore the effects of actions by the police, courts, probation and prisons on G&T individuals and communities; (iii) interviews with local professionals who have engaged with G&Ts in a variety of contexts, both operationally and strategically (e.g. police officers, Victim Support, housing officers, councillors, Police and Crime Commissioners). These will seek to find out the ways in which G&Ts and their lifestyles are understood and responded to in formal policies and operationally on the ground, as well as documenting where support services may need to be targeted in criminal justice and other service provision; and (iv) archival research of governmental and other publically available historical sources, including council committee meeting minutes, county surveys of G&Ts' experience of policing and local petitions against official sites. Taken together, these methods will provide, for the first time, numerical estimates of both victimisation and offending, whilst also illuminating the meaning attached to them by G&Ts, including the place of perceptions of racism in G&Ts' behaviour and experiences. The study will provide insight into how criminal justice and other statutory agencies have historically dealt with G&Ts compared with the contemporary picture. In this way it will build a sensitive account of G&Ts' experiences of crime as victims as well as offenders which can respond to the negative stereotyping of G&Ts drawing on rigorous evidence. This will inform policy and practice so as to reduce the harms of crime for all those affected, in both G&T and non-G&T communities.